Effect of underbody diffuser on the aerodynamic drag of vehicles in convoy. Issue 1 (31st December 2016) - Aulakh, Deepinder Jot Singh
Abstract: Presented work is extension to previous studies of convoying where prime focus was to study effect of intervehicular spacing and upperbody geometry of vehicles on aerodynamics of convoy. Current study examines the effect of underbody diffuser on coefficient of drag (Cd) of convoy of two reference car bodies (Ahmed body). CFD analysis of convoy is done using Shear-Stress-Transport model under moving ground conditions. The length of lead body's diffuser is taken as 0.222 m with diffuser angle (degrees) of 0 (no diffuser), 3, 5, 7, 9, 15, 20, 25 and 30 each at intervehicular spacing of 0.25 and 0.75 Ahmed body length. Each configuration thus resulting was analyzed with lead body backlite angle of 25° (pre-critical) and 35° (post-critical) with follow body's backlite angle remaining 25°. CFD analysis are conducted after performing two validation analyses from previous studies. To understand the flow features developed on Ahmed body due to an underbody diffuser a preliminary analysis is done on an isolated body with 25° and 35° backlite angles by applying each diffuser angle used in current study. After analysis of convoy, drag on lead and follow vehicles is found to be also dependent on the axial vortices formed due to diffuser in addition to those from backlite surface of lead body. Average drag on cases with diffuser is found to be lesser than the no diffuser cases up to a certain diffuser angle. Thus applying diffuser has a potential for reducing the overall drag on convoy.